2002
DOI: 10.1046/j.1440-1711.2002.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Tamm‐Horsfall protein to complement 1q and complement 1, including influence of hydrogen‐ion concentration

Abstract: SummaryThe goal of this study was to further characterize the interaction between an abundant urinary glycoprotein, Tamm-Horsfall protein, and complement 1q to determine the robustness of this reaction under different environmental conditions (particularly pH) and to begin to determine the specificity of this reaction. The influence of pH coupled with ionic strength was evaluated with an ELISA that demonstrated immobilized TammHorsfall protein bound complement 1q strongly with a K D in the nmol/L range from pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…However, Moonen et al [37] reported that THP could not bind with native cytokines including TNF-α. In addition, the binding of THP to complement 1 and complement 1q depends on the electrostatic evens as demonstrated by the influence of hydrogen concentration and ionic-strength on THP-C1q binding affinity [16,38]. In this study, we found that enzymatic digestion of THP with neuraminidase or β-galactosidase did not significantly affect the binding activity with different protein molecules, although a tendency of decrease was shown in Figs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, Moonen et al [37] reported that THP could not bind with native cytokines including TNF-α. In addition, the binding of THP to complement 1 and complement 1q depends on the electrostatic evens as demonstrated by the influence of hydrogen concentration and ionic-strength on THP-C1q binding affinity [16,38]. In this study, we found that enzymatic digestion of THP with neuraminidase or β-galactosidase did not significantly affect the binding activity with different protein molecules, although a tendency of decrease was shown in Figs.…”
Section: Discussionmentioning
confidence: 52%
“…The daily excretion of THG ranges from 50-200 mg in humans [32]. The glycoprotein can interact with viral proteins [1], bacterial structure components [2], bacterial exotoxin [33], immunoglobulin light chains [14,15], complement component 1 and 1q [16], proinflammatory cytokine IL-1 [12], IL-2 [34] and TNF-α [12,13], and surface membrane proteins on human PMN, lymphocytes and monocytes [17][18][19][20][21]. Immunologically, THG not only activates PMN through binding to a single class of sialic acid-specific cell surface receptors [17] but enhances the release of IL-1, IL-6, and TNF-α from monocytes responsible for B and T lymphocytes proliferation [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, uromodulin has been shown to induce pro-inflammatory cytokine release from human whole blood [8], to activate myeloid dendritic cells (DC) to acquire a fully mature DC phenotype [9], and to activate monocytes [8]. Precisely how uromodulin orchestrates these diverse immunological properties is unknown, however the protein has been shown to bind with high affinity to a number of immuno-proteins including the complement factors C1, C1q and C3 [10,11], IgG [12,13] and cytokines such as TNF alpha, IL-1 beta and IL-8 [14]. It is thought that these diverse but potent pro-inflammatory properties of uromodulin may signal tubular damage and repair [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The trapping role played by urinary THP may not be limited to cytokines. Previous in vitro studies suggested that THP also binds to complement C1 and C1q (61)(62)(63). It is possible that THP is a promiscuous urinary trap not only for cytokines, but also for other immunological effectors.…”
Section: Discussionmentioning
confidence: 99%